JFK : public, private, secret [large type] - Taraborrelli, J. Randy (Thorndike Press large print biographies and memoirs., 2025)
"In this deeply researched presidential biography, J. Randy Taraborrelli tells John F. Kennedy's story in a provocative new way by revealing how public moments in his life were so influenced by private relationships with not only his family, but also Jackie's. But it's the secret life that also surprises. As Congressman, Senator and finally President, JFK was a magnet for women. With exclusive interviews and meticulous research, Taraborrelli reveals not only the man's many affairs but also the strength and resolve his wife showed in coping with them"--